2016
DOI: 10.3389/fbuil.2016.00027
|View full text |Cite
|
Sign up to set email alerts
|

Life-Cycle Cost Model and Design Optimization of Base-Isolated Building Structures

Abstract: Design of economic structures adequately resistant to withstand during their service life, without catastrophic failures, all possible loading conditions and to absorb the induced seismic energy in a controlled manner, was subjected to intensive research so far. Costly and extremely sensitive equipment, vital in commerce, business, education, and/or health care represent the contents of the contemporary structural systems. Frequently, structures themselves are less valuable than their contents. Moreover, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The references of Table 1 present the expected loss ratios for buildings under the earthquake excitations. Because these ratios are dimensionless, they have been used in different sites (e.g., previous studies [2][3][4][5][6][7] ).…”
Section: Life-cycle Cost Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The references of Table 1 present the expected loss ratios for buildings under the earthquake excitations. Because these ratios are dimensionless, they have been used in different sites (e.g., previous studies [2][3][4][5][6][7] ).…”
Section: Life-cycle Cost Analysismentioning
confidence: 99%
“…[ 1 ] Therefore, in recent studies, the life‐cycle cost has been the seismic optimization goal of designing the control system for retrofitting (or seismic design) the structures. [ 2–9 ] Mitropoulou and Lagaros [ 3 ] investigated the performance and cost of seismic isolators using life‐cycle cost analysis. They showed that although the seismic isolator system is expensive, the life‐cycle cost is less than its fixed counterpart.…”
Section: Introductionmentioning
confidence: 99%
“…However, the explicit quantification of uncertainties is still a major challenge (Takewaki, 2015). The development of appropriate methods for uncertainty quantification will receive much attention in the years to come with different computational models such as fuzzy analysis, classical probabilities, probabilistic hazard analysis (Mori et al, 2017), methods for uncertainty quantification such as robust design, reliability-based design (Lagaros et al, 2007), life-cycle optimal design (Mitropoulou and Lagaros, 2016), sensitivity analysis and others. These methods will create new opportunities to meet the long-standing challenge of delivering quantitative predictivity in computational mechanics and engineering.…”
Section: Modeling Of Uncertaintiesmentioning
confidence: 99%
“…In addition, the capacity spectrum method, applying the pushover analysis approach, was presented by the Federal Emergency Management Agency (2013), while many other researchers worked with the dynamic time history analysis method for the life-cycle cost assessment of buildings such as the ones performed by Porter et al (2004), Lagaros (2007), Mitropoulou et al (2011), Gencturk et al (2016) Loli et al (2017), Sharmin et al (2018), Rabonza and Lallemant (2019), and Noureldin and Kim (2021). Besides, in another field, several other research works have been published with the focus on the application of vibration control systems in the reduction of buildings’ life-cycle cost (Park et al, 2004; Gidaris and Taflandis, 2012, 2015; Mitropoulou and Lagaros, 2016). The main disadvantage of all works, similar to the mentioned ones, is missing the aftershock effects in the evaluation of the life-cycle cost due to earthquake scenarios.…”
Section: Introductionmentioning
confidence: 99%